Hormone withdrawal-associated symptoms: Comparison of oestradiol valerate/dienogest versus ethinylestradiol/norgestimate. (August 2013) - Jensen, Jeffrey T.; Parke, Susanne; Mellinger, Uwe; Serrani, Marco; Mabey, R. Garn
Abstract Objectives To determine the effect of oestradiol valerate/dienogest (E2V/DNG) versus ethinylestradiol/norgestimate (EE/NGM) on hormone-withdrawal associated symptoms (HWAS) in otherwise healthy women who had experienced at least one of these symptoms when using 21/7-day combined oral contraceptives (COCs). Methods This phase III, parallel-group study randomised 409 women aged 18 to 50 years to E2V/DNG or EE/NGM. The primary efficacy variable was the change from baseline to cycle 6 in the average of the three highest visual analogue scale values for headache and/or pelvic pain during cycle days 22 to 28. Results In total, 395 were included in the full analysis set (E2V/DNG, n = 191; EE/NGM, n = 204). E2V/DNG reduced the symptoms of headache or pelvic pain during cycle days 22 to 28 from baseline to cycle 6 to a significantly greater extent than EE/NGM (mean decrease 43.6 vs. 35.5 mm; p = 0.0024). Both treatments were well tolerated with a similar proportion of women experiencing adverse events that were considered at least possibly related to treatment (35% E2V/DNG vs. 34% EE/NGM). Conclusions E2V/DNG reduces the frequency and intensity of headache and pelvic pain to a greater extent than EE/NGM, and may be a good option for women susceptible to HWAS with conventional 21/7-day COCs.